The Effect Of Intellectual Intelligence And Emotional Intelligence On Auditor Performance With Organizational Commitment And Spiritual Intelligence As Moderating Variables - Al Amin, Roy (Universitas Lancang Kuning, 2025)
This study examines the influence of intellectual and emotional intelligence on auditor performance, with organizational commitment and spiritual intelligence as moderating variables. The research involved 150 auditors working at Public Accounting Firms (PAFs) in West Sumatra, Riau, and the Riau Islands, using purposive sampling. Data analysis was conducted with Structural Equation Modeling using Partial Least Squares (SEM-PLS). The findings show that both intellectual and emotional intelligence significantly affect auditor performance. Organizational commitment strengthens the relationship, while spiritual intelligence provides partial support, though its direct effect on performance is not significant. The study also reveals that emotional intelligence exerts a stronger impact compared to intellectual intelligence. These results highlight the importance of emotional management and organizational commitment in enhancing motivation and performance. The contribution of this study lies in its support for Motivation Theory and its practical implications for PAFs to design training programs that integrate intellectual and emotional intelligence development to improve auditor performance overall.